Synthesis and Dielectric Properties of MgO:ZnO Composites - Hasan, Ahmad A. (Iraqi Journal of Science, 2022)
The dielectric properties of the fabricated composites MgO:ZnO with various mixing ratios (100,75:25,50:50,25:75, and 100 wt. %)were investigated. The structure analysis was conducted using X-ray diffraction. The structure phase, crystallite size and purity of the fabricated MgO:ZnO composites were confirmed using X-ray diffraction spectra. The results declared that the diffraction spectrum of 100%MgO composite samples were compatible with cubic structure along the plane (200) while the structures of residual composite's samples were compatible with hexagonal structures. The crystal size of the most pronounced plane (101) for crystal growth was changed from 30.4 nm to 53.2 nm by increasing ZnO ratio from 25 to 100wt%. The dielectric properties were studied as function of frequency over the range (50Hz-10MHz). The a.c conductivity σa.c(ω) showed power low dependence for the full frequency range except for the composites samples of 0 and 75 %wt. ZnO which showed d.c region in the low frequency range. The exponent (s) values which represents the slope of ln σa.c(ω) and ln(ω) changed in non-regular manner by increasing the ZnO ratio. The dielectric constant ε1 and the dielectric loss ε2 increased with the increase of the ZnO ratio up to 75% ZnO and then decreased with further increase of ZnO ratio. The dielectric loss peaks observed in the plot diagram of ε2 against ln(ω)  is found to shift towards the high-frequency side which indicates the decrease of relaxation time and prompt  movement of charge carriers .The polarizability values (α)  estimated from the COLE –COLE diagram increased  from 0.112 to 0.467  when the ratio of ZnO changed from 0 to 50wt.% which referred to reduction of the intermolecular forces. While (α) reduced drastically at 75wt.% ZnO which referred to the growing of the intermolecular forces.